The neurophysiology of intraoperative error: An EEG study of trainee surgeons during robotic-assisted surgery simulations - D'Ambrosia, Christopher; Aronoff-Spencer, Eliah; Huang, Estella Y.; Goldhaber, Nicole H.; Christensen, Henrik I.; Broderick, Ryan C.; Appelbaum, Lawrence G. (Frontiers in Neuroergonomics, 2023)
Surgeons operate in mentally and physically demanding workspaces where the impact of error is highly consequential. Accurately characterizing the neurophysiology of surgeons during intraoperative error will help guide more accurate performance assessment and precision training for surgeons and other teleoperators. To better understand the neurophysiology of intraoperative error, we build and deploy a system for intraoperative error detection and electroencephalography (EEG) signal synchronization during robot-assisted surgery (RAS). We then examine the association between EEG data and detected errors. Our results suggest that there are significant EEG changes during intraoperative error that are detectable irrespective of surgical experience level.